CROSS-NATIONAL VARIABILITY IN SEX/GENDER DIFFERENCES AND LATER-LIFE MEMORY: INDIA AND THE UNITED STATES. (20th December 2022) - Westrick, Ashly; Avila-Rieger, Justina; Gross, Alden; Kobayashi, Lindsay
Abstract: Little is known about the extent of sex/gender differences in later-life cognitive health in low-income countries such as India. We compared sex/gender differences in later-life memory, overall and by educational attainment, across men and women aged ≥65 years in India and the United States. Data were from Harmonized Cognitive Assessment Protocols (HCAP) in the population-representative Longitudinal Study of Aging in India (LASI; N=4, 096;) and U.S. Health and Retirement Study (HRS; N=3, 345). Multiple-group models estimated interactions between sex/gender and educational attainment on harmonized episodic memory scores across countries. In the U.S., women had a memory performance advantage compared to men across all education levels. In India, men had a memory performance advantage compared to women overall, interactions revealed that this advantage was only present among those with no formal education. Among those with at least lower secondary education, women demonstrated an advantage that increased with increasing education.